Integration of circular economy into design and construction of infrastructure projects in Malaysia: Barriers and countermeasures - Nor Helmie Shahreen, Mohd Ali; Lee, Yong Siang; Ahmad Rizal, Alias; Rahimi, A. Rahman (Malaysian Institute of Planners, 2024)
Despite the high demands of infrastructures, circular economy (CE) is among the best solution that seeks holistic sustainability goals through a zero-waste culture and to boost economic growth by investing in eco-innovations, secondary raw materials, recycling processes, and industrial symbiosis. Therefore, this study aims to identify the barriers and countermeasures for integrating the CE concept into design and construction of infrastructure projects in Malaysia. For data collection, an open-ended interview has been carried out with twenty-three (23) respondents of clients, contractors, and consultants. Then, the thematic analysis was performed to analyse the data. The findings suggested that the main barriers of CE integration are consisted of internal and external factors; technical, organisational, economic, political, social and environmental aspects. Then, the countermeasures of CE integration are categorized into the hard and soft strategies; raising the awareness of CE, encouraging stakeholder’s collaboration and creating financial incentives, and investment opportunities. As a result, the outcome of the findings can serve as a guideline for stakeholders to integrate CE concept into design and construction of infrastructure projects in order to achieve sustainability development goals (SDG). Through the outcome of this study, stakeholders will have a new approach and new paradigm, which will be useful for future decision-making on the infrastructure with the CE concept.